Strong band filling induced significant excited state absorption in MAPbI3 under high pump power. (August 2020) - Chen, B.A.; Pang, G.T.; Lan, X.Q.; He, Z.B.; Chen, R.
Abstract: Perovskite has been considered as promising material for solar cell application. Understanding the carrier dynamics in perovskite material plays a vital role for further improvement of the power conversion efficiency of solar cells. In this article, carrier dynamics of MAPbI3 under different pump powers have been investigated by ultrafast pump-probe transient absorption spectroscopy. Complete processes of carrier cooling and recombination under different pump powers have been characterized and compared carefully. It is found that a significant carrier band filling happened during cooling process under high pump power, which results in a strong excited state absorption at the photon energy of 2.353 eV. High carrier density induced strong Auger effect appears not only in the band edge but also the higher conduction band. And subsequently, a large part of carriers keeps hot for more than 5 ns indicating that MAPbI3 is meaningful for hot carrier extraction in solar cells. A critical carrier concentration of 9.32 × 10 17  cm −3 has been determined at which Auger effect starts to work. It could provide some guidance for perovskite solar cell application. Graphical abstract: Image 1 Highlights: Significant excited state absorption in MAPbI3 is observed under high pump power and a strong carrier band filling effect is found. The energy structure of MAPbI3 with two conduction bands is proposed. The carrier dynamics are fitted and the critical carrier concentration of 9.32 × 10 17  cm −3 is determined for the strong Auger effect to happen.